2019
DOI: 10.1080/21870764.2019.1604609
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different sodium-based additives on corrosion resistance of PEO coatings on pure Ti

Abstract: In the present study, the plasma electrolytic oxidation method was used to form ceramic coatings on pure Ti substrates. For this purpose, five different aluminate-based electrolytes containing various sodium-based additives (sodium hydroxide, sodium phosphate, sodium silicate, sodium tetraborate and sodium fluoride) were used. The role of additives in the growth, macrostructure, surface and cross-sectional microstructure, phase composition and corrosion resistance of the coatings was evaluated. An X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…As soon as the applied voltage reaches the breakdown potential of the previously formed film, various sparking phenomena appear, leading to the formation of discharge channels, where temperature and pressure achieve higher values and different processes, such as melting and oxidation, may occur. During the PEO process, molten oxides may migrate through the discharge channels and then are rapidly cooled, generating an uneven microstructure with well-separated micropores, similar to a volcano-crater shape [ 9 ]. When DC is applied, the oxidized titanium surface presents numerous irregularities and open pores, which may be attributed to the intense gas evolution that takes place during the oxidation process.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As soon as the applied voltage reaches the breakdown potential of the previously formed film, various sparking phenomena appear, leading to the formation of discharge channels, where temperature and pressure achieve higher values and different processes, such as melting and oxidation, may occur. During the PEO process, molten oxides may migrate through the discharge channels and then are rapidly cooled, generating an uneven microstructure with well-separated micropores, similar to a volcano-crater shape [ 9 ]. When DC is applied, the oxidized titanium surface presents numerous irregularities and open pores, which may be attributed to the intense gas evolution that takes place during the oxidation process.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that PEO-modified titanium from a silicate-containing solution presents better osteointegration compared to untreated titanium [ 20 ]. Several studies in the literature confirm the significant effect of the electrolyte composition on the corrosion behavior of the PEO-developed coatings [ 9 , 13 ]. Shokouhfar et al [ 13 ] concluded that changing the electrolyte composition without altering the rest of the process parameters has led to an increase in pores size generated on the surface of the samples, and furthermore, the corrosion resistance was considerably affected.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations